Etnobotani Tanaman Obat Sebagai Imunomodulator di Desa Adi Luhur Kecamatan Panca Jaya Provinsi Lampung - Setyaningsih, Erwi Putri; Febriyanti, Risma (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2023)
An ethnobotanical study was conducted to see the interaction of local people with their environment and to study the relationship between humans and their surrounding plants. The people in Adi Luhur Village have used traditional medicinal plants for a long time as evidenced by the existence of a women's farmer group in Adi Luhur Village. Each house has a family of medicinal plants to meet the needs of herbal medicines that can be used to prevent or treat disease. This study aims to determine the types of immunomodulatory plants used by the people in Adi Luhur Village, Panca Jaya District, Lampung Province. The type of research was observational using descriptive qualitative research methods. Sampling was carried out in the community of Adi Luhur Village, Panca Jaya District, Lampung Province by purposive sampling. The sample was determined based on the similarity between characteristics and inclusion criteria including the people of Adi Luhur Village who are willing to be respondents and fill out a questionnaire, people who have consumed herbal medicine in the last one month, and people in the age range of 20-75 years. Filling out the questionnaire involved a respondent of 110 people. Determination of the number of samples based on Lameshow calculations of the total population of 1.989 people. Based on the results of the study, information was obtained that in Adi Luhur Village 5 plants were cultivated and could be used as immunomodulators, namely sambiloto, turmeric, ginger, lempuyang, and finger root which are consumed by boiling and then drinking. The part of the plant that was taken for the leaves is sambiloto, while the parts for the rhizome were ginger, turmeric, lempuyang, and finger root.